The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/horticulturae8040300
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Response of Malus domestica Borkh cv. Rubin Apple to Canopy Training Treatments in Intensive Orchards

Abstract: In this study, we used apple tree (Malus domestica Borkh.) cv. Rubin grafts on dwarfing P60 rootstock. Our planting scheme was single rows with 1.25 m between trees and 3.5 m between rows. The aim of this study was to determine the impact of canopy training treatments, as a stress factor, on metabolic response to obtain key information on how to improve physiological behavior and the management of the growth and development of apple trees. The results indicated that all applied canopy training treatments signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…It has been observed that the amount of varied compounds within plant tissues are potentially determined by a multitude of factors, such as genotype [ 31 , 32 ], species [ 4 , 33 ], leaf age and seasonal variations [ 34 , 35 ], growth site [ 35 ], stress [ 36 ], and extraction methodology [ 13 , 14 , 20 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that the amount of varied compounds within plant tissues are potentially determined by a multitude of factors, such as genotype [ 31 , 32 ], species [ 4 , 33 ], leaf age and seasonal variations [ 34 , 35 ], growth site [ 35 ], stress [ 36 ], and extraction methodology [ 13 , 14 , 20 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since phenolic compounds and antioxidants are involved in protection from both biotic and abiotic stressors [ 36 , 41 ], it is worth investigating whether either early or late bud burst oak phenotypes may produce larger amounts of them in their tissues and thus the bark of oaks with this phenotype would potentially be more beneficial for extracting bioactive compounds of phenolic or antioxidant origin.…”
Section: Introductionmentioning
confidence: 99%
“…Different rootstocks have different effects on fruit quality [16]. Dwarf apple rootstocks can improve fruit color, significantly increase single-fruit weight and first-grade fruit yield, increase fruit hardness, and improve intrinsic fruit quality [17,18]. Dwarf citrus rootstocks can maintain tree-vigor stability and have no significant effect on nutrient content [19].…”
Section: Introductionmentioning
confidence: 99%
“…Sirgedait ė-Š ėžien ė et al [6] used 'Rubin' apple trees grafted on dwarfing P60 rootstocks to determine the impact of canopy training treatments as a stress factor on metabolic response to obtain key information on how to improve physiological behaviour and the management of growth and development of apple trees. The results indicated that all applied canopy training treatments significantly increased the total phenol and total starch contents in apple tree leaves.…”
mentioning
confidence: 99%